Assessment of possible uncertainties arising during the hydromorphological monitoring of a Sand-Bedded Large River - Právetz Tamás; Sipos György; Ladányi Zsuzsanna (Journal of Environmental Geography, 2017)
The riverbed morphology of sand-bedded rivers is dynamically changing as a consequence of quasi continuous bedload transport. In the meantime, the dimension, size and dynamics of developing bedforms is highly depending on the regime of the river and sediment availability, both affected by natural and anthropogenic factors. Consequently, the assessment of morphological changes as well as the monitoring of riverbed balance is challenging in such a variable environment. In relation with a general research on the longer term sediment regime of River Maros, a fairly large alluvial river in the Carpathian Basin, the primary aim of the present investigation was to assess uncertainties related to morphological monitoring, i.e. testing the reproducibility of hydromorphological surveys and digital elevation model generation by performing repeated measurements among low water conditions on selected representative sites. Surveys were conducted with the combination of an ADCP sonar, GPS and total station. The most appropriate way of digital elevation modelling (DEM) was tested and 30-point Kriging was identified to be optimal for comparative analysis. Based on the results, several uncertainties may affect the reproducibility of measurements and the volumetric deviation of DEM pairs generated. The mean horizontal difference of survey tracks was 3-4 m in case of each site, however this could not explain all the DEM deviation. Significant riverbed change between measurements could also be excluded as the main factor. Finally, it was found that results might be affected greatly by systematic errors arising during motor boat ADCP measurements. Nevertheless, the observed, normalised and aggregated DEM uncertainty (600-360 m3/rkm) is significantly lower than the changes experienced between surveys with a month or longer time lag. Consequently, the developed measurement strategy is adequate to monitor long term morphological and sediment balance change on sand bedded large river.